2006
DOI: 10.1094/mpmi-19-0123
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Engineered Resistance to Fusarium Head Blight in Wheat by Expression of Arabidopsis NPR1

Abstract: Fusarium head blight (FHB) is a devastating disease of wheat and barley which causes extensive losses worldwide. Monogenic, gene-for-gene resistance to FHB has not been reported. The best source of resistance to FHB is a complex, quantitative trait derived from the wheat cv. Sumai 3. Here, we show that the Arabidopsis thaliana NPR1 gene (AtNPR1), which regulates the activation of systemic acquired resistance, when expressed in the FHB-susceptible wheat cv. Bobwhite, confers a heritable, type II resistance to F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
238
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 311 publications
(256 citation statements)
references
References 41 publications
12
238
0
1
Order By: Relevance
“…Results obtained in this study confirm that several defense-related genes are induced at higher levels in the AtNPR1 transformants compared to their non-transgenic counterparts. Similar results, showing higher-level induction of downstream defense genes, have been obtained by others in wheat and apple (Makandar et al 2006;Chen et al 2012). It is interesting that the WT plants show little, if any, induction of these defense-related genes.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Results obtained in this study confirm that several defense-related genes are induced at higher levels in the AtNPR1 transformants compared to their non-transgenic counterparts. Similar results, showing higher-level induction of downstream defense genes, have been obtained by others in wheat and apple (Makandar et al 2006;Chen et al 2012). It is interesting that the WT plants show little, if any, induction of these defense-related genes.…”
Section: Discussionsupporting
confidence: 88%
“…Similar limitations were observed in the AtNPR1 transformants against Verticillium wilt, where protection was observed only against the non-defoliating isolates of V. dahliae and not the defoliating isolates (Parkhi et al 2010b). Nevertheless, there are a large number of reports that show that NPR1 overexpression confers a strong protection against a variety of diseases (Lin et al 2004;Makandar et al 2006;Malnoy et al 2007;Wally et al 2009;Zhang et al 2010;Dutt et al 2015;Silva et al 2015). Thus, controlled expression of NPR1 gene may still prove to be a useful means to confer tolerance to some pathogens in the field.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…For example, the NPR1 gene is a central regulator in both monocots and dicots. The NPR1 gene was successfully used in several plant species like Arabidopsis (Cao et al 1998), rice (Chern et al 2001), tomato (Ekengren et al 2003), and wheat (Makandar et al 2006). Similarly, the mlo gene functions in barley (Peterhänsel and Lahaye 2005), tomato (Bai et al 2008), and Arabidopsis (Consonni et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Of these, 3 were sterile and 8 were silenced in later generations. Consequently the final transformation efficiency of transcriptionally active transgenic Alvarez et al (2000), Anand et al (2003), Makandar et al (2006) and Chen et al (2008), who also observed silencing during the early generations of selfing in transgenic plants. Gene silencing is usually associated with integration of transgenes in multiple copies and to sequence homology between a transgene and an endogenous gene.…”
Section: Discussionmentioning
confidence: 95%